2018
DOI: 10.9788/tp2018.1-02en
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome in Bank Employees: A Literature Review

Abstract: This study aims to identify the empirical studies that investigate the prevalence of and factors associated with burnout syndrome in bank employees that were published in the PUBMED, SciELO, LILACS, MEDLINE, PsycINFO, ISI Web of Knowledge and Science Direct indexers, and to analyze such studies with regard as to the research methods they used. Fourteen studies were identifi ed that were grouped into the socio-demographic, personal, organizational and labor variables related to burnout. The sample size ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 28 publications
0
8
2
11
Order By: Relevance
“…One example of poor working conditions associated with a negative effect on physical health and thereby with high levels of stress and burnout is that the majority of bank employees are required to work while being seated for the entire working day. More generally, according to recent studies (Dias and Angelico, 2018;Giorgi et al, 2017), employees who are subjected to extended excessive demands in the workplace have a higher risk of WS that leads to physical burnout than employees for whom this is not the case.…”
Section: Burnoutmentioning
confidence: 99%
“…One example of poor working conditions associated with a negative effect on physical health and thereby with high levels of stress and burnout is that the majority of bank employees are required to work while being seated for the entire working day. More generally, according to recent studies (Dias and Angelico, 2018;Giorgi et al, 2017), employees who are subjected to extended excessive demands in the workplace have a higher risk of WS that leads to physical burnout than employees for whom this is not the case.…”
Section: Burnoutmentioning
confidence: 99%
“…It should be noted that the development of burnout affects not only health and education workers, but also other professionals who experience episodes of intense stress and tension, such as police officers, coaches and bankers. 12,13,14 Scientific studies have found that health care workers are often developing stress and burnout, especially in hospital settings. [5][6][7][8][9][10][11][12][13][14][15] Long working hours, low pay and work overload are factors that lead to the development of the disorder by the nursing staff and were mentioned by the interviewees.…”
Section: Discussionmentioning
confidence: 99%
“…Češće se javlja kod zaposlenih koji tokom radnog procesa ostvaruju bliski kontakt sa drugim ljudima, koji su u poziciji da im je potrebna neka vrsta pomoći, u tzv. pomagačkim zanimanjima [3] . Pojedine studije ukazuju da je prevalenca sindroma izgaranja oko 30% kod nastavnika, 31% kod studenata medicine, a između 44% i 68% kod onkologa [4] .…”
Section: Uvodunclassified